2022
DOI: 10.3390/su14116383
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Wild Cotton Gossypium aridum in Mexico Using Flowering Growing Degree Days and Annual Available Soil Water

Abstract: Climate change is expected to alter species distribution and habitat composition, with wild species being particularly vulnerable. Gossypium aridum, a wild cotton species in Mexico, has shown a decrease in habitat extent and population; however, the data are not precise. The objectives of this study are: (1) to develop a distribution model of G. aridum in Mexico, (2) to identify areas with environmental conditions similar to where the species currently maintains populations, and (3) to determine which variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Some studies have demonstrated good predictive ability even with only three variables [67]. For this study, we considered the following variables because of their importance to the cotton plant [2,15,[68][69][70][71]: annual available soil water (mm year −1 , AASW), Flowering Growing Degree Days (FGDD), absolute minimum temperature ( • C, Tminabs), and altitude (amsl, ALT).…”
Section: Environmental Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated good predictive ability even with only three variables [67]. For this study, we considered the following variables because of their importance to the cotton plant [2,15,[68][69][70][71]: annual available soil water (mm year −1 , AASW), Flowering Growing Degree Days (FGDD), absolute minimum temperature ( • C, Tminabs), and altitude (amsl, ALT).…”
Section: Environmental Parametersmentioning
confidence: 99%
“…Flowering Growing Degree Days: the variable Growing Degree Days (GDD), also known as Heat Units (HUs) or thermal time, reflects the relationship between growth rate and temperature and refers to the specific amount of heat units that plants require to develop from one stage of development to another [15,[77][78][79][80]. In the present study, we considered Flowering Growing Degree Days (FGDD), which refers to the necessary GDD to cover the flowering phase, the prime physiological stage of the cotton plant that determines the final productivity [2,71]. It is calculated as follows:…”
Section: Environmental Parametersmentioning
confidence: 99%